Dialog Ayah Dan Anak Dalam Al-Qur’an: Analisis Tafsir Maqashidi Terhadap Fenomena Fatherless - Zahrotun, Zahrotun; Anwar, Mohammad Khoiril (UIN Sultan Syarif Kasim Riau, 2023)
This article aims to explore the forms of paternal parenting dialogues in Surah Luqman: 13 and Surah Ash-Shaffat: 102, along with the wisdom behind the use of the term 'father' (ayah). Additionally, the researcher aims to identify the maqashid values within these two verses to address the phenomenon of fatherlessness. Fatherlessness has become a hotly discussed issue in the context of parenting, considering the increasingly modern family conditions, economic pressures, and the marginalized role of fathers as primary educators. The research method employed is thematic (maudhu'i) exegesis with a maqashidi approach. The issues to be addressed include the forms of dialogue between fathers and children in the Qur'an and the phenomenon of fatherlessness from a maqashidi exegesis perspective. The research results indicate that the phenomenon of fatherlessness contradicts the ideal role of a father as explicitly depicted in the stories of Luqman and Prophet Ibrahim in the Qur'an. The paternal role consists of three levels: biological, material provision, and loyalty. However, various factors, including economic, social, and personal emotional aspects, may hinder optimal functionality. In alignment with the understanding of the paternal role, the fatherlessness phenomenon in millennial family life can be minimized. Fathers need to recognize that, in addition to their role in meeting material needs, they play a crucial part in shaping the character and future of their children. The maqashid from Surah Luqman 13 and Surah Ash-Shaffat 102, depicting paternal dialogue, emphasize his responsibility in parenting, addressing the fatherless phenomenon, encompassing six primary maqashid, especially hifzh ad-din (preservation of religion) and hifzh al-nasl (preservation of lineage). Abstrak: Tulisan ini bertujuan untuk mengetahui bentuk-bentuk dialog pengasuhan ayah dalam QS. Luqman: 13 dan QS. Ash-Shaffat: 102 beserta hikmah di balik penggunaan diksi ayah. Selain itu peneliti juga ingin menemukan nilai-nilai maqashid dari kedua ayat tersebut dalam upaya menjawab adanya fenomena fatherless (ketidakhadiran atau kurangnya peran ayah). Fatherless menjadi isu yang hangat dibicarakan dalam konteks pengasuhan, mengingat kondisi keluarga yang makin modern, tekanan ekonomi dan peran ayah sebagai pendidik primer makin terpinggirkan. Metode yang digunakan dalam riset adalah tafsir tematik (maudhu’i) dengan pendekatan tafsir maqashidi. Adapun masalah yang hendak dijawab adalah, bagaimana bentuk-bentuk dialog antara ayah dan anak di dalam Al-Qur’an serta bagaimana fenomena fatherless perspektif tafsir maqashidi. Hasil riset ini menunjukkan bahwa fenomena fatherless tidak sesuai dengan bagaimana seharusnya seorang ayah berperan yang secara jelas dikisahkan oleh Luqman dan nabi Ibrahim dalam ayat-ayat Al-Qur’an. Peran ayah terdiri dari tiga tingkatan; tingkat biologis, tingkat pemenuhan kebutuhan materi, dan tingkat kesetiaan. Akan tetapi beberapa faktor meliputi ekonomi, sosial, dan emosional personal menyebabkan ketidakberfungsian secara maksimal. Sejalan dengan pemahaman peran ayah, fenomena fatherless di kehidupan keluarga milenial bisa diminimalisir. Ayah harus menyadari bahwa selain perannya dalam memenuhi kebutuhan materi, ia memiliki peran yang sangat penting dalam membentuk karakter dan masa depan anak. Maqashid dari QS. Luqman 13 dan QS. Ash-Shaffat 102 tentang dialog ayah yang menggambarkan perannya sebagai tanggungjawab parenting di balik fenomena fatherless meliputi enam maqashid terutama hifzh ad-din dan hifzh al-nasl.